Visual pigments and spectral sensitivity of juvenile sutchi catfish (Pangasianodon hypophthalmus Sauvage 1878) - Tan, Nai-Han; Mukai, Yukinori; Okawa, Ryo; Anraku, Kazuhiko (Wiley, 2018)
Knowledge on the visual spectral sensitivity of a given fish is important for determi‐ nation of optimal light conditions for improvement of fish rearing in aquaculture. Sutchi catfish (Pangasianodon hypophthalmus Sauvage 1878) is an important freshwa‐ ter fish species in Southeast Asia. The present study aimed to understand the visual spectral sensitivity of juvenile sutchi catfish through spectrophotometric measure‐ ment of the spectral absorbance of wholemounts of retinae. The spectral absorbance curves obtained from the spectrophotometric measurement indicated a parabolic shape. The curves for retinae photo‐bleached with initial flash of blue, green and yel‐ low lights, respectively had a peak at approximately 560 nm, which were the same as the curve for retinae photo‐bleached with broad wavelength light. On the other hand, the curve for retinae photo‐bleached with initial flash of red light had a peak shifted prominently toward shorter light wavelength at approximately 540 nm. This prominent shift of peak implied that the retinae of juvenile sutchi catfish absorb light wavelength of red. Therefore, the present results clearly suggested that juvenile sutchi catfish utilises longer light wavelengths.